2008
DOI: 10.1098/rsif.2008.0425.focus
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected porous hydroxyapatite ceramics for bone tissue engineering

Abstract: Several porous calcium hydroxyapatite (HA) ceramics have been used clinically as bone substitutes, but most of them possessed few interpore connections, resulting in pathological fracture probably due to poor bone formation within the substitute. We recently developed a fully interconnected porous HA ceramic (IP-CHA) by adopting the 'foam-gel' technique. The IP-CHA had a three-dimensional structure with spherical pores of uniform size (average 150 mm, porosity 75%), which were interconnected by window-like hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
133
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(143 citation statements)
references
References 38 publications
1
133
0
9
Order By: Relevance
“…In 1997, Tsurga and coworkers implied that the optimal pore size of bioceramics that supported ectopic bone formation was 300 -400 μm [454]. Thus, there is no need to create calcium orthophosphate bioceramics with very big pores; however, the pores must be interconnected [95,384,397,398]. Interconnectivity governs a depth of cells or tissue penetration into the porous bioceramics, as well as it allows development of blood vessels required for new bone nourishing and wastes removal [455,456].…”
Section: Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, Tsurga and coworkers implied that the optimal pore size of bioceramics that supported ectopic bone formation was 300 -400 μm [454]. Thus, there is no need to create calcium orthophosphate bioceramics with very big pores; however, the pores must be interconnected [95,384,397,398]. Interconnectivity governs a depth of cells or tissue penetration into the porous bioceramics, as well as it allows development of blood vessels required for new bone nourishing and wastes removal [455,456].…”
Section: Porositymentioning
confidence: 99%
“…Namely, porous HA bioceramics can be colonized by bone tissues [381,[386][387][388][389][390][391][392][393][394][395][396]. Therefore, interconnecting macroporosity (pore size > 100 μm) [111,374,381,397,398], which is defined by its capacity to be colonized by cells, is intentionally introduced in solid bioceramics (Fig. 6).…”
Section: Porositymentioning
confidence: 99%
“…Another important characteristic of HAp is its biodegradability. Previous studies [7][8][9][10][11][12] have shown that hydroxyapatite tends not to trigger a response from the immune system, embedding itself successfully in the surrounding tissue and degrading over time as the host tissue begins to regenerate.…”
Section: Introductionmentioning
confidence: 99%
“…Interconnected porous hydroxyapatite ceramic (IP-CHA) materials with high porosity have been developed and used successfully in the field of orthopedics medicine (10). An IP-CHA block, which consists of a porous sintered body composed of hydroxyapatite ceramics with a unique pore structure, is able to undergo extensive incorporation into host bone more rapidly than conventional porous calcium hydroxyapatite ceramic (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…An IP-CHA block, which consists of a porous sintered body composed of hydroxyapatite ceramics with a unique pore structure, is able to undergo extensive incorporation into host bone more rapidly than conventional porous calcium hydroxyapatite ceramic (10,11). We speculated that problems associated with autogenous block bone grafting could be avoided if an IP-CHA block of the same size as an autogenous block bone were to be used for onlay grafting.…”
Section: Introductionmentioning
confidence: 99%